The Fourth Market theory and interest rate benchmarking in the Islamic finance industry - Ahmed Tahiri Jouti (ISRA International Journal of Islamic Finance, 2021)
Purpose - This paper aims to understand the issue of interest rate benchmarking in Islamic financial institutions (IFIs) from a macro-economic perspective and assessing the relevance of creating a Sharīʿahcompliant profit rate benchmark to solve this issue. This paper also aims at suggesting an Islamic alternative that will handle both the negative economic impact on IFIs as well as on their financial performance. Design/methodology/approach - The paper is based on literature review of conventional finance and Islamic finance theories to construct a theoretical model to assess the impact of interest rate benchmarking on the ability of IFIs to achieve the objectives of the Islamic economy. Findings - The macro-economic perspective concludes that conceiving a profit rate benchmark for the Islamic finance industry is not relevant to raising the Sharīʿah credibility of the industry. Indeed, several adjustments need to be introduced in terms of the business model. Research limitations/implications - The recommendations of this paper require the involvement of financial authorities and governments for their implementation. Indeed, the adjustments require a macroeconomic review. Practical implications - The paper considers a profit rate benchmark irrelevant and inefficient. Instead, it suggests the necessary adjustments in terms of business model and economic approach for IFIs to achieve their objectives. Social implications - The paper considers zakat implementation and the adjustment of IFIs as the real path to implement a fair wealth distribution in the society. Originality/value - The creation of a profit rate benchmark has always been the only solution for the pricing issue in IFIs. This paper challenges this idea and tries to give a deeper understanding of the situation.
Keywords: 330; Interest rate benchmark; Price control in Islam; Profit rate benchmark; Zakat